Exfoliative Cheilitis More than an Aesthetic Problem: Case Report - Boza-Oreamuno, Yadira V.; Mena-Lizano, Andrés (Odovtos - International Journal of Dental Sciences, 2022)
Exfoliative cheilitis (EC) is a rare and chronic inflammatory condition. It is characterized by a continuous peeling of the vermilion of the lips and abnormal production of keratin scales. Treatment is difficult due to its chronic nature and it is often refractory. The objective of this article is to describe the management of EC and its impact on quality of life through two clinical cases. Two patients with EC are reported: one 21 years old with allergic rhinitis and gastric reflux, the other 18 years old, with a history of anxiety symptoms, without medication or psychiatric control. They had chronic scaly and crusty areas on both lip vermilions. In one of the patients, a biopsy was prescribed and he was treated with antifungals and topical vitamin E. Both patients were prescribed hydration, balanced diet, the application of moisturizing lip balm with sunscreen and modification of parafunctional habits, behavioral aid. The treatment healed the condition and eased their daily life and improved personal perception. Nibbling and lip licking favor dryness and superinfection in patients with EC; for its part, hydration, topical vitamin E and behavioral aid, improved this condition.